Aprendizagem socioemocional : um olhar dos professores da educação básica - Santos, Diana Leonhardt dos (2023)
Historically, cognitive aspects of learning such as test performance and knowledge tests related to reading, writing and math have always been prominent in school curriculums. However, this view has been changing over the years. Since the launch of the Law of Directives and National Educational Bases in 1996 (BRAZIL, 1996), the need for basic education schools to act on the full formation of students has been stressed. With the homologation of the National Core Curriculum in 2017, the incentive towards socio-emotional development of students has become more evident. In face of this scenario, the present thesis has as its general objective to investigate the conceptions of primary school teachers on socio-emotional learning and how they approach this theme at the schools they work. The specific objectives are: (a) to investigate what the conceptions of primary school (1st to 5th year) teachers on socio-emotional learning are; (b) to analyze what pedagogic strategies teachers use for the students’ socio-emotional development; (c) to investigate if the teachers feel prepared and supported by the school to work with socio-emotional learning; (d) propose, based on the needs found, central themes for continuous teacher training. In order to achieve the objectives of this thesis, we carried out a case study in a private basic education school in the city of Porto Alegre. 54 primary school teachers participated, being subjected to three tools: (a) Teacher’s Perceptions of Schooling Socio-Emotional Needs Inventory (MOREIRA et al., 2013); (b) Teacher SEL Beliefs Scale (BRACKETT et al., 2012); (c) Questionnaire made by the Ph.D. candidate named “Questionnaire of Pedagogic Practices for Socio-Emotional Learning”. Tools (a) and (b) were translated by a specialist from the area, as these are tools originally created in English. For quantitative data analysis, we carried out a survey of the frequency of responses; for qualitative data, we used the principles of Bardin’s content analysis. The findings showed that most teachers understand socio-emotional learning as related to both intra-personal aspects (recognition and management of emotions) and inter-personal aspects (caring and worrying towards others, establishment of healthy relationships and assertive conflict resolution). Most teachers pointed out that the socio-emotional needs they observe in their students are intra-personal, i.e. related to self-conscience and self-management. The pandemic was mentioned as one of the factors that accentuated the students’ difficulties. Regarding the strategies most used by the participants for students’ socio-emotional development, giving room for listening and dialogue was the strategy mostly mentioned. The collected data allowed us to think about central themes for continuous primary school teacher training concerning the investigated topic.